2011
DOI: 10.1016/j.jpainsymman.2011.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Advance Care Planning in Belgium and The Netherlands: A Nationwide Retrospective Study Via Sentinel Networks of General Practitioners

Abstract: Context. Advance care planning (ACP) is an important part of patient-centered palliative care. There have been few nationwide studies of ACP, especially in Europe.Objectives. To investigate the prevalence and characteristics of ACP in two European countries and identify the associated factors.Methods. A mortality follow-back study was undertaken in 2007 via representative nationwide Sentinel Networks of general practitioners (GPs) in Belgium and The Netherlands using similar standardized procedures. All GPs re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
91
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(110 citation statements)
references
References 29 publications
11
91
0
6
Order By: Relevance
“…Over half (13) of the included studies used qualitative methodology such as interviews and focus groups. Three studies employed mixed methodology such as surveys combined with interviews or open-ended questions.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over half (13) of the included studies used qualitative methodology such as interviews and focus groups. Three studies employed mixed methodology such as surveys combined with interviews or open-ended questions.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…11 The goal of optimising quality of life during incurable illness is also a central tenet of palliative care, and ACP allows the differing preferences of individuals to be identified, documented and enacted. [12][13][14] This synergy of purpose has driven interest in embedding ACP as a fundamental aspect of palliative care. 15,16 Accordingly, ACP in palliative care has been focused upon in international conferences, national health policy in several countries and the popular media.…”
Section: Introductionmentioning
confidence: 99%
“…10e12 Family members are often consulted in end-of-life care decisions, 13 and a high percentage of medical decisions are made by surrogates. 14,15 Some research has explored the perspectives of family members regarding decisionmaking. 14,16e21 A few studies revealed patterns or types of decision-making and showed that relatives have varying preferences in terms of level and scope of involvement in decisionmaking.…”
mentioning
confidence: 99%
“…Conformément à ce qui a été décrit [8], les MGs de notre étude s'estimaient pour la plupart disponibles (78,1 %) et compétents (81,2 %) pour participer à ce type de décision. Tout comme leurs collègues réanimateurs, deux études ont montré que les MGs étaient régulièrement amenés à prendre en ville des décisions de LAT pour leurs patients [9,10]. Ces constatations vont dans le sens des dernières recommandations du Conseil national de l'ordre des médecins et de la Société de réanimation de langue française (SRLF) [11][12][13] : les MGs semblent être parmi ceux les plus aptes à endosser ce rôle de consultant défini par la loi pour les personnes inconscientes hospitalisées en réanima-tion.…”
Section: Caractéristiques Des Mgsunclassified